Math Games : 180 Reproducible Activities to Motivate, Excite, and Challenge Students, Grades 6-12 - Muschla, Judith A. ((Jossey-Bass Teacher. Grades 6-12), 2004)
Contenido: 1) Números enteros; 2) Fracciones, decimales y porcentajes; 3) Geometría; 4) Medición; 5) Algebra; 6) Análisis de datos; 7) Potpurrí.